When competition fails to optimise quality: a look at search engines - Stucke, M; Ezrachi, A (Yale Law School, 2016)
The European Commission's Statement of Objections forms the latest addition to the ongoing debate on the possible misuse of Google's position in the search engine market. The scholarly debate, however, has largely been over the exclusionary effects of search degradation. Less attention has been dedicated to the dimension of quality - whether and how a search engine, faced with rivals, could degrade quality on the free side. We set out to address this fundamental question: with the proliferation of numerous web search engines and their free usage and availability, could any search engine degrade quality? We begin our analysis with a review of the network effects that may impact the relative power of a search engine. We next identify three necessary, but not sufficient, variables for quality degradation to occur in search results. With these three variables in mind, we consider instances when a search engine could degrade quality despite competition from rivals.